2022
DOI: 10.1371/journal.pone.0274257
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling identifies candidate biomarkers for new latent tuberculosis infections. A cohort study

Abstract: Objective To determine the gene expression profile in individuals with new latent tuberculosis infection (LTBI), and to compare them with people with active tuberculosis (TB) and those exposed to TB but not infected. Design A prospective cohort study. Recruitment and follow-up were conducted between September 2016 to December 2018. Gene expression and data processing and analysis from April 2019 to April 2021. Setting Two male Colombian prisons. Participants 15 new tuberculin skin test (TST) converters (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…A number of genomic studies have recently been conducted to identify a set of genetic factors underlying susceptibility to TB including UBE3A [ 11 , 12 ], chromosome region 8q12–q13 [ 13 ], VDR, IL12, Il12RB1, INFG, MBL, DRB1, SFTPA1/2, and NRAMP1 [ [14] , [15] , [16] , [17] ], MCP1 [ 18 , 19 ], chromosomes 2q21-2q24 and 5p13-5q22 for PTST-, chromosome 7p22-7p21 for TB [ 20 ], TST1 and TST2 [ 21 ], TNF1 [ 22 ], and CCL1 [ 23 ]. More specifically, genetic variants participating directly in human immunity such as interleukin (IL)-10, interferon (IFN)-γ, and nitric oxide synthase 2 play key roles in susceptibility to TB [ [24] , [25] , [26] , [27] , [28] ]. Additionally, previous studies have revealed the important roles of epigenetic modifications of a number of genes including NRAMP1, IFNG, NOS2A, VDR, ISG15, TACO, TLR1, TLR, IL18R1, PADI, DUSP14, and MBL, NLRP-3 , and MASP-2 in TB susceptibility [ [29] , [30] , [31] , [32] ].…”
Section: Introductionmentioning
confidence: 99%
“…A number of genomic studies have recently been conducted to identify a set of genetic factors underlying susceptibility to TB including UBE3A [ 11 , 12 ], chromosome region 8q12–q13 [ 13 ], VDR, IL12, Il12RB1, INFG, MBL, DRB1, SFTPA1/2, and NRAMP1 [ [14] , [15] , [16] , [17] ], MCP1 [ 18 , 19 ], chromosomes 2q21-2q24 and 5p13-5q22 for PTST-, chromosome 7p22-7p21 for TB [ 20 ], TST1 and TST2 [ 21 ], TNF1 [ 22 ], and CCL1 [ 23 ]. More specifically, genetic variants participating directly in human immunity such as interleukin (IL)-10, interferon (IFN)-γ, and nitric oxide synthase 2 play key roles in susceptibility to TB [ [24] , [25] , [26] , [27] , [28] ]. Additionally, previous studies have revealed the important roles of epigenetic modifications of a number of genes including NRAMP1, IFNG, NOS2A, VDR, ISG15, TACO, TLR1, TLR, IL18R1, PADI, DUSP14, and MBL, NLRP-3 , and MASP-2 in TB susceptibility [ [29] , [30] , [31] , [32] ].…”
Section: Introductionmentioning
confidence: 99%